2014
DOI: 10.1007/s10096-013-2035-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Escherichia coli isolated from hospitalised children and adults with urinary tract infection

Abstract: Urinary tract infection (UTI) is common amongst children and recurs in 10-30 % of cases. The differences between Escherichia coli strains causing UTI among hospitalised children and adults remains to be fully elucidated. Here, we examined the genetic relatedness and virulence gene (VG) profiles of a collection of E. coli causing UTI among hospitalised children and adults. Genetic relatedness among the strains was investigated using random amplified polymorphic DNA (RAPD) analysis and the strains were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
1
10
1
3
Order By: Relevance
“…In Jahrom city, the prevalence of papG, afaC, sfa, fimH, ibeA, and iucD were 53.3%, 51.7%, 53.3%, 56.7%, 20%, and 73.3%, respectively which were mostly similar to findings of the present survey [27]. There was a difference between children and adults regarding the prevalence of hlyA, kpsMII and ibeA among UPEC [28], but this was concluded in our study. Momtaz in Shahrekord found that fimH virulence gene was detected in 86.17% of UPEC isolates, and 2.43% of them belonged to the O1, O2, O6, O7 and O16 serogroups [29].…”
Section: Discussionsupporting
confidence: 84%
“…In Jahrom city, the prevalence of papG, afaC, sfa, fimH, ibeA, and iucD were 53.3%, 51.7%, 53.3%, 56.7%, 20%, and 73.3%, respectively which were mostly similar to findings of the present survey [27]. There was a difference between children and adults regarding the prevalence of hlyA, kpsMII and ibeA among UPEC [28], but this was concluded in our study. Momtaz in Shahrekord found that fimH virulence gene was detected in 86.17% of UPEC isolates, and 2.43% of them belonged to the O1, O2, O6, O7 and O16 serogroups [29].…”
Section: Discussionsupporting
confidence: 84%
“…Escherichia coli isolated from drinking water were screened for the presence of selected virulence genes usually associated with the E. coli strains responsible for extra-intestinal infections, including: fyuA (yersiniabactin receptor), kpsMTII (capsular polysaccharide genes), and papC [P fimbriae, ( 30 )]. In order to detect the genes agn 43 [antigen 43, ( 31 )], fimH [minor component of type 1 fimbriae, ( 32 )], hlyA [haemolysin, ( 33 )], and afa [afimbrial adhesins, ( 30 )] a multiplex PCR was designed with the following conditions: 94°C for 5 min followed by 40 cycles of 30 sec at 94°C, 1 min at 60°C and 1 min at 68°C with a final elongation step at 72°C for 10 min. For the sequences of the primers see Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In our study fluB gene, associated with reduced cell aggregation and less biofilm production, was carried by a single commensal E. coli isolate. Vollmerhausen and Katouli reported agn43b, coded by flu B gene was prevalent among E. coli isolates in hospitalized children with urinary tract infections from Australia [23]. Our study tested only two extra-intestinal pathogenic E. coli (ExPEC) associated virulence markers and it is a limitation of our study.…”
Section: Ctx-m-15 + Shv-12 + Qnrs + Aac(6')-ib-crmentioning
confidence: 92%